2021
DOI: 10.1007/s00228-020-03058-w
|View full text |Cite
|
Sign up to set email alerts
|

The influence of recipient SLCO1B1 rs2291075 polymorphism on tacrolimus dose–corrected trough concentration in the early period after liver transplantation

Abstract: Purpose To explore the relationship between rs2291075 polymorphism in SLCO1B1 gene, which encodes an influx transmembrane protein transporter, and tacrolimus dose–corrected trough concentration (C/D, ng ml−1 mg−1 kg−1) in the early period after liver transplantation. Methods CYP3A5 rs776746 and SLCO1B1 rs2291075 polymorphisms of 210 liver transplantation patients and their corresponding donor livers were assessed by PCR amplification and DNA sequencing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…SLCO1B1 encodes the protein of organic anion transporting polypeptide 1B1, is highly expressed in the liver and is involved in the biliary excretion of tacrolimus. 26 , 27 CHST10 (Carbohydrate Sulfotransferase) encodes an enzyme adds sulfate to glucuronic acid to form a carbohydrate antigen, HNK -1 that is capable of transferring sulfate to glucuronidated steroid hormones and other lipophilic drugs to facilitate their excretion via urine. 28 The three recipient SNPs in the model suggested that drug distribution/elimination in extrahepatic organs such as intestine may be especially important in the early phase since the liver-related drug elimination may be weak before the restoration of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…SLCO1B1 encodes the protein of organic anion transporting polypeptide 1B1, is highly expressed in the liver and is involved in the biliary excretion of tacrolimus. 26 , 27 CHST10 (Carbohydrate Sulfotransferase) encodes an enzyme adds sulfate to glucuronic acid to form a carbohydrate antigen, HNK -1 that is capable of transferring sulfate to glucuronidated steroid hormones and other lipophilic drugs to facilitate their excretion via urine. 28 The three recipient SNPs in the model suggested that drug distribution/elimination in extrahepatic organs such as intestine may be especially important in the early phase since the liver-related drug elimination may be weak before the restoration of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…The synonymous variant rs2291075 in Gene SLCO1B1, which has been previously associated with the pharmacokinetics of tacrolimus and some chemotherapeutic drugs [31,32], and which was present in 91 heterozygous and 66 homozygous children, was associated with response to HU treatment through the recessive model, its presence being an advantage. Gene SLCO1B1 encodes for an organic anion transporting polypeptide, the OATP1B1, HU being one substrate of this transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Shu et al reported SLCO1B1 rs2306283 polymorphism association with TAC blood concentrations 16 . A recently published study concluded that SLCO1B1 rs2291075 is probably a new variant associated with TAC metabolism 17 …”
Section: What Is New and Conclusionmentioning
confidence: 99%
“…study concluded that SLCO1B1 rs2291075 is probably a new variant associated with TAC metabolism. 17 According to available data, influx and efflux transporters have an important role in TAC pharmacokinetics/pharmacodynamics. 13 However, due to often controversial results and a small number of appropriate designed pharmacogenomics studies, there is an urgent need to raise the attention of clinicians and researchers to the pharmacogenomics of TAC.…”
Section: Co N Fli C T O F I Nte R E S Tmentioning
confidence: 99%